Vitamin D3 Prevents the Deleterious Effects of Testicular Torsion on Testis by Targeting miRNA-145 and ADAM17: In Silico and In Vivo Study - Doaa I. Mohamed; Doaa A. Abou-Bakr; Samar F. Ezzat; Hanaa F. Abd El-Kareem; Hebatallah H. Abo Nahas; Hosam A. Saad; Amir E. Mehana; Essa M. Saied (MDPI AG, 2021)
Testicular torsion (TT) is the most common urological emergency in children and young adults that can lead to infertility in many cases. The ischemia-reperfusion (IR) injury due to TT has been implicated in the pathogenesis of testicular damage. The main pathological mechanisms of contralateral injury after ipsilateral TT are not fully understood. In the presented study, we investigated the molecular and microscopic basis of ipsilateral and contralateral testicular injury following ipsilateral testicular torsion detorsion (T/D) and explored the possible protective role of vitamin D3. The biochemical analysis indicated that IR injury following T/D significantly decreased the activity of testicular glutathione peroxidase (GPx) enzyme, level of serum testosterone, serum inhibin B, and expression of testicular miRNA145, while increased the activity of testicular myeloperoxidase (MPO) enzyme, level of testicular malondialdehyde (MDA), level of serum antisperm-antibody (AsAb), and expression of ADAM-17. The histological and semen analysis revealed that torsion of the testis caused damages on different tissues in testis. Interestingly, administration of vitamin D3 prior to the IR injury reversed the deterioration effect of IR injury on the testicular tissues as indicated by biochemical and histological analysis which revealed normal appearance of the seminiferous tubules with an apparent decrease in collagen fiber deposition in both ipsilateral and contralateral testes. Our results revealed that the protective effect of vitamin D3 treatment could be attributed to target miRNA145 and ADAM17 protein. To further investigate these findings, we performed a detailed molecular modelling study in order to explore the binding affinity of vitamin D3 toward ADAM17 protein. Our results revealed that vitamin D3 has the ability to bind to the active site of ADAM17 protein via a set of hydrophobic and hydrophilic interactions with high docking score. In conclusion, this study highlights the protective pharmacological application of vitamin D3 to ameliorate the damages of testicular T/D on the testicular tissues via targeting miRNA145 and ADAM17 protein.